2004
DOI: 10.1533/joti.2003.0065
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Transverse Yarn-on-solid Coefficient of Friction

Abstract: The transverse friction coefficient of a yarn sliding on a surface is much more difficult to measure than its lengthwise coefficient. A method based on the transverse sliding of the yarn on the cylindrical balloon limiter of a two-for-one twister is proposed to measure this coefficient. A simple yarn ballooning apparatus based on a hollow spindle was built and tested. A top picture of the cylindrically constrained yarn balloon is taken and the final yarn angle is measured. This angle can be theoretically corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Studies investigating dry fabric frictions can be found in the textile scientific community, [33][34][35][36][37][38][39][40][41][42] and are among the most relevant over the past few years. However, the yarns are different from those used in composite reinforcements, in terms of mechanical properties and geometry.…”
Section: Processes Of the Lcm (Liquid Composite Moulding) Family Sucmentioning
confidence: 99%
“…Studies investigating dry fabric frictions can be found in the textile scientific community, [33][34][35][36][37][38][39][40][41][42] and are among the most relevant over the past few years. However, the yarns are different from those used in composite reinforcements, in terms of mechanical properties and geometry.…”
Section: Processes Of the Lcm (Liquid Composite Moulding) Family Sucmentioning
confidence: 99%